Malay speech recognition using hidden Markov model method - 355948 Ting, Kang Syn (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2006